‘This restless enemy of all fertility’: exploring paradigms of coastal dune management in Western Europe over the last 700 years - Clarke, Michèle L.; Rendell, Helen M. (Wiley, 2015)
Drifting sand has inundated settlements and damaged agricultural land along the coasts of Western Europe for the last 700 years. The need to control sand migration has been an important driver of the management of coastal sand dunes and here we analyse original archival materials to provide new insights into historically changing coastal dune management practices. Records of coastal sand movement in Denmark, The Netherlands, Britain, Ireland and France were reviewed and three distinct management approaches were identified. The ways in which these approaches have played out in space and time were examined with particular reference to records from landed estates in Britain and Ireland. We demonstrate how historical evidence can be used to inform contemporary debates on dune management strategy and practice. We propose a new place-based approach to the future management of coastal dunes that can incorporate both expert and locally produced ‘knowledges’ and that is underpinned by an understanding of how both natural forces and human interventions have shaped these dune landscapes over time.